What works in crime prevention?: comparison and critical review of three crime prevention registries - Fagan, Abigail A. (Criminology & public policy, 2016)
This article compares the criteria and methods applied by three registries designed to identify what works in crime and delinquency prevention. We discuss and demonstrate how variation in the methodological rigor of these processes affects the number of interventions identified as “evidence based” and provide recommendations for future list-making to help increase the dissemination of effective crime prevention programs and practices.